2015
DOI: 10.3174/ajnr.a4239
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Time-Attenuation Curve Blood Flow Parameters in Patients with and without Carotid Stenosis

Abstract: BACKGROUND AND PURPOSE:From the time-attenuation curves of DSA flow parameters, maximal intensity, maximal slope, and full width at half maximum of selected vascular points are defined. The study explores the reliability of defining the flow parameters by the time-attenuation curves of DSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
3
10
0
Order By: Relevance
“…The study of Lin et al showed significant change at M1 and M2 only. 10 Our study showed significant changes for all arterial ROIs except A2. The discrepancy in maximal slope (WI in our Results for the hemodynamic parameters with significant changes (P < .05) after the stenting procedure in the PA view study) and FWHM is most likely caused by the difference in calculation algorithm.…”
Section: In 2012supporting
confidence: 47%
See 4 more Smart Citations
“…The study of Lin et al showed significant change at M1 and M2 only. 10 Our study showed significant changes for all arterial ROIs except A2. The discrepancy in maximal slope (WI in our Results for the hemodynamic parameters with significant changes (P < .05) after the stenting procedure in the PA view study) and FWHM is most likely caused by the difference in calculation algorithm.…”
Section: In 2012supporting
confidence: 47%
“…Lin et al 10 reported a study of cerebral circulation time by calculating the rTTP relative to the cervical ICA on the PA view (same location as ICA 1 in our report) and relative to the cavernous segment of the ICA on the lateral view (same location as ICA 2 in our report). We found that the poststenting mean circulation times of M1, M2, and PV (corresponding to rTTP of the following segments: ICA 1 -M1, ICA 2 -M2, and ICA 2 -PV) in our study (0.49, 0.50, and 4.14 seconds, respectively) were close to those of healthy controls (0.46, 0.58, and 4.38 seconds, respectively).…”
Section: In 2012mentioning
confidence: 67%
See 3 more Smart Citations